Implementasi Perubahan Tata Ruang Kawasan Tambang dalam Rangka Kepastian Hukum di Provinsi Jambi - Sarwani, Raden (Universitas Batanghari Jambi, 2025)
Regional Spatial Planning (RTRW) serves as a guideline for policy development, including long-term regional development plans, medium-term regional development plans, industrial development plans, and investment implementation in the region Law Number 15 of 2019. The establishment of the RTRW in the form of regional regulations (PERDA) provides a strong legal basis for regional governments to direct development, maintain environmental sustainability, prevent conflicts due to overlapping land use, and support sustainable economic growth without neglecting ecological aspects, as well as creating a balance between development and environmental preservation. In an effort to achieve the goals of the state, national development is carried out by all components of the nation and in its implementation there have been two changes to the spatial planning policy of Jambi province since the enactment of Jambi provincial regulation number 9 of 1993The Jambi Province spatial planning plan is no longer in line with regional, economic, political, and environmental developments, resulting in a decline in the quality of space in the Jambi Province region. The research method used is normative juridical, namely a study that focuses on legal norms, legal principles, and legal systems related to the issues discussed. The research findings show that changes in the spatial planning of mining areas in Jambi Province are the result of a complex interaction between internal and external factors, including economic, policy, environmental, social, and the dynamics of national spatial planning law. Internal factors such as the potential for large coal resources, limited logistics infrastructure, and the need for mining infrastructure development have driven changes in the spatial structure and spatial patterns of the region. Furthermore, enforcing compliance with spatial planning is key to directing mining activities to comply with sustainability principles and applicable laws.